The oral Janus kinase/spleen tyrosine kinase inhibitor ASN002 demonstrates efficacy and improves associated systemic inflammation in patients with moderate‐to‐severe atopic dermatitis: results from a randomized double‐blind placebo‐controlled study. (6th May 2019) - Bissonnette, R.; Maari, C.; Forman, S.; Bhatia, N.; Lee, M.; Fowler, J.; Tyring, S.; Pariser, D.; Sofen, H.; Dhawan, S.; Zook, M.; Zammit, D.J.; et al.
Summary: Background: ASN002 is an oral dual inhibitor of Janus kinase and spleen tyrosine kinase, which are involved in the pathogenesis of atopic dermatitis (AD) through their regulatory role on T helper (Th)1, Th2 and Th17/Th22 pathways. Objectives: The objectives of this study were to evaluate the efficacy, safety, pharmacokinetics and effects on systemic biomarkers of ASN002 in patients with moderate‐to‐severe AD. Methods A total of 36 patients with moderate‐to‐severe AD were randomized (3 : 1) to ASN002 or placebo in the phase Ib study. Three dosage cohorts were studied over a 28‑day period (20 mg, 40 mg and 80 mg once daily). Results: ASN002 was superior to placebo for the proportion of patients achieving Eczema Area and Severity Index (EASI) 50 (20 mg 20%, P = 0·93; 40 mg 100%, P = 0·003; 80 mg 83%, P = 0·03; placebo 22%), EASI 75 (20 mg 0%, P = 0·27; 40 mg 71%, P = 0·06; 80 mg 33%, P = 0·65; placebo 22%) and in change from baseline in pruritus (20 mg −1·3 ± 2·1, P = 0·81; 40 mg −3·1 ± 2·7, P = 0·27; 80 mg −4·7 ± 2·1, P = 0·01; placebo −1·6 ± 1·8). Adverse events were generally mild and similar across all groups. ASN002 showed dose‐dependent plasma exposure with low interpatient variability, significantly downregulated several serum biomarkers involved in Th1, Th2 and Th17/Th22 immunity, and decreased the atherosclerosis‐associated biomarker E selectin/SELE. Conclusions: In patients with moderate‐to‐severe AD, ASN002 showed strong efficacy with rapid onset of action and associated improvements in systemic inflammation. Abstract : What's already known about this topic? Currently available therapeutic options for atopic dermatitis (AD) include topical corticosteroids, calcineurin inhibitors, crisaborole, dupilumab, ciclosporin and phototherapy. However, few oral treatments are available and those are associated with safety concerns. What does this study add? ASN002, an oral, dual Janus kinase and spleen tyrosine kinase inhibitor, was well tolerated and showed promising efficacy and rapid onset of action in patients with moderate‐to‐severe AD at daily doses of 40 mg and 80 mg. The encouraging efficacy, safety and tolerability profile of ASN002 warrant further investigation of ASN002 in patients with moderate‐to‐severe AD. Linked Comment:  Lebwohl. Br J Dermatol 2019; 181 :658 . Plain language summary available online Respond to this article